Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Theophylline increases diaphragmatic contractility in mechanically ventilated newborns. - De Cunto, Angela; Paviotti, Giulia; Bua, Jenny; Demarini, Sergio (J Crit Care, 2017)
Keywords: Diaphragm; Humans; Infant, Newborn; Muscle Contraction; Theophylline

Body mass index curves for Italian preterm infants are comparable with American curves for infants born before 34 weeks of gestational age. - Paviotti, Giulia; Monasta, Lorenzo; Ronfani, Luca; Montico, Marcella; Copertino, Marco; De Cunto, Angela; Demarini, Sergio (Acta Paediatr, 2016)
AIM: Body mass index (BMI)-for-age curves have been developed in the USA, but not compared with other populations. This study created gender-specific intrauterine BMI-for-age curves for Italian preterm infants and compared them with the USA version. METHODS: Data on 92 262 newborn infants, born at 26-42 weeks of gestational age in the north-eastern Italian region of Friuli Venezia Giulia between 2005 and 2013, were analysed to create gender-specific BMI-for-age curves. Gender-specific and age-specific BMI Z scores for Italian infants were calculated using the parameters of the USA growth curves and the World Health Organization charts. RESULTS: Gender-specific BMI-for-age at birth curves were developed for premature Italian infants from 26 gestational weeks. The comparison with the USA charts showed no significant difference in BMI percentiles in Italian infants born at ≤33 gestational weeks, but infants born at ≥34 gestational weeks had a significantly higher BMI than the USA population, by 0.2 standard deviations. CONCLUSION: We developed the first European BMI-for-age at birth curves for premature infants. According to our findings, the Italian curves were comparable to the USA curves for the subgroup of infants born at ≤33 gestational weeks, but not ≥34 gestational weeks.

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors

From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

When does postnatal catch-up fat occur in late preterm infants? - De Cunto, Angela; Paviotti, Giulia; Demarini, Sergio (Acta Paediatr, 2014)
Keywords: Body Composition; Humans; Infant, Premature

More on prolonged pacifier usage and risk of dental problems: an Italian survey of current clinical practice. - De Cunto, Angela; Minen, Federico; Ventura, Alessandro (J Pediatr Nurs, 2013)
Keywords: Female; Guidelines as Topic; Humans; Male; Pacifiers; Sudden Infant Death

Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria

Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed

A case of familial hemiplegic migraine associated with a novel ATP1A2 gene mutation. - De Cunto, Angela; Bensa, Marco; Tonelli, Alessandra (Pediatr Neurol, 2012)
Hemiplegic migraine constitutes an unusual form, characterized by periodic attacks of migraine with a motor component (hemiplegia). Familial forms are dominantly inherited, and are attributable to mutations in genes encoding proteins involved in ion transportation, including ATP1A2, which codes for the α-2 isoform of the sodium-potassium adenosine triphosphatase, a P-type cation transport adenosine triphosphatase, and responsible for the so-called familial hemiplegic migraine type 2. We describe a 9-year-old boy affected by familial hemiplegic migraine, with a novel ATP1A2 gene mutation (c.1799T>C p.V600A) in exon 13. Long-term treatment with flunarizine resulted in a good clinical response and the prevention of further attacks.
Keywords: Amino Acid Sequence; Child, Preschool; Humans; Male; Migraine with Aura; Molecular Sequence Data; Mutation; Pedigree; Sodium-Potassium-Exchanging ATPase

Delayed diagnosis of glycogen storage disease type III. - Minen, Federico; Cont, Gabriele; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro; Maggiore, Giuseppe; Faletra, Flavio; Gasparini, Paolo; Cassandrini, Denise (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Delayed Diagnosis; Diagnostic Errors; Glycogen Storage Disease Type I; Glycogen Storage Disease Type III; Humans; Infant; Liver; Male

Antidepressant drugs and breastfeeding: a review of the literature. - Davanzo, Riccardo; Copertino, Marco; De Cunto, Angela; Minen, Federico; Amaddeo, Alessandro (Breastfeed Med, 2011)
The use of antidepressants in breastfeeding mothers is controversial: Manufacters often routinely discourage breastfeeding for the nursing mother despite the well-known positive impact that breastfeeding carries on the health of the nursing infant and on his or her family and society. We conducted a systematic review of drugs commonly used in the treatment of postpartum depression. For every single drug two sets of data were provided: (1) selected pharmacokinetic characteristics such as half-life, milk-to-plasma ratio, protein binding, and oral bioavailability and (2) information about lactational risk, according to some authoritative sources of the literature: Drugs in Pregnancy and Lactation edited by Briggs et al. (Lippincott Williams, Philadelphia, 2008), Medications and Mothers' Milk by Hale (Hale Publishing, Amarillo, TX, 2010), and the LactMed database of TOXNET ( www.pubmed.gov ; accessed June 2010). Notwithstanding a certain variability of advice, we found that (1) knowledge of pharmacokinetic characteristics are scarcely useful to assess safety and (2) the majority of antidepressants are not usually contraindicated: (a) Selective serotinin reuptake inhibitors and nortryptiline have a better safety profile during lactation, (b) fluoxetine must be used carefully, (c) the tricyclic doxepine and the atypical nefazodone should better be avoided, and (d) lithium, usually considered as contraindicated, has been recently rehabilitated.
Keywords: Adrenergic Uptake Inhibitors; Antidepressive Agents; Antidepressive Agents, Tricyclic; Biological Availability; Breast Feeding; Depression, Postpartum; Directive Counseling; Drug Monitoring; Female; Humans; Infant, Newborn; Lactation; Lithium Compounds; Maternal Exposure; Milk, Human; Monoamine Oxidase Inhibitors; Pregnancy; Serotonin Uptake Inhibitors

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome

An unusual case of buccal obstruction: the antrochoanal polyp. - De Cunto, Angela; Minen, Federico (Arch Dis Child, 2011)
Keywords: Adolescent; Cheek; Female; Humans; Mouth Diseases; Nasal Obstruction; Nasal Polyps; Oropharynx